3D Holo-Learning Based on Holograms as an Interactive Learning Media for High School Students in Malang District - Muhaimin, Rizal; Abdillah, Ghauts Mannah Aji; Sulfa, Devi Mariya; Mandandari, Delia; Christian, Coryan Wira; Setiawan, Deny (Proceeding International Conference on Religion, Science and Education, 2024)
The quality of Indonesian education is still relatively low. Indonesia is ranked 54th out of 78 countries below Slovenia regarding the quality of education. Learning in Indonesia still uses a generalist theoretical approach which does not apply technology in delivering the material which has an impact on the lack of development of creativity and expertise in the field of science and technology. This means that education is unable to produce students who are qualified and ready to compete. The application of technology in learning can be one solution in improving the quality of education. The quality of education has increased by applying advanced technology in learning to develop student learning outcomes. The application of technology in learning can be done by developing technology-based learning media, one of which is 3D holo-learning. 3D holo-learning learning media uses holograms as the technology used in learning. Holograms as a learning medium are able to visualize abstract material into concrete and adaptive ones. This research was conducted to develop 3D holo-learning as an interactive learning media for class XII high school students. The research method used is the ADDIE method. At the development stage, trials were carried out in small groups at high school on nervous system material. Based on the results of this trial, the learning effectiveness was quite effective at a percentage of 59%. The application was also carried out at the implementation stage for class.